Experimental study of oil plume stability: Parametric dependences and optimization. Issue 1 (15th October 2016) - Li, Haoshuai; Shen, Tiantian; Bao, Mutai
Abstract: Oil plume is known to interact with density layer in spilled oil. Previous studies mainly focused on tracking oil plumes and predicting their impact on marine environment. Here, simulated experiments are presented that investigated the conditions inducing the formation of oil plume, focusing especially on the effects of oil/water volume ratio, oil/dispersant volume rate, ambient stratification and optimal conditions of oil plume on determining whether a plume will trap or escape. Scenario simulations showed that OWR influences the residence time most, dispersants dosage comes second and salinity least. The optimum residence time starts from 2387 s, occurred at approximately condition (OWR, 0.1, DOR, 25.53% and salinity, 32.38). No change in the relative distribution under the more scale tank was observed, indicating these provide the time evolution of the oil plumes. Graphical abstract: Highlights: The oil/water volume ratio influences the residence time most, the dosage of dispersants comes second and salinity least. The optimum residence time occurred at approximately condition (OWR, 0.1, DOR, 25.53% and salinity, 32.38). No change in the relative distribution under the more scale tank was observed.